(untitled) (Journal of Global Humanities and Social Sciences, 2023)
With the increasingly fierce competition in the global market, the demand of enterprises to improve supply chain efficiency is becoming more and more urgent. As one of the valuable resources of enterprises, human resources play an important role in optimizing supply chain efficiency. Based on this, this paper will analyze the impact of human resource optimization on supply chain efficiency based on performance management from the aspects of employee performance, teamwork, talent training, and process design to provide useful reference and guidance for enterprises to improve supply chain operational efficiency.